Transformation of Space Discourse: from Traditional Society to Postmodern Era - V. A. Shchipkov (Vestnik MGIMO-Universiteta, 2015)
The paper examines the problem of transforming the perception of space in the paradigms of several cultural epochs. Space discourse is defined via its societal perception, reflection in mythological systems and some philosophical concepts. The author reviews the history of changes of space discourse through continued development of two stages - traditional and post-traditional. The author refers the archaic society, the Antiquity and the Middle Ages to the traditional stage, the Renaissance, the Modernity and the Postmodernity to the post-traditional. The author examines each of these stages and describes mythological and holistic perception of space in archaic society, its further development and hierarchizing in the Antiquity, as well as transfer of the main features of the Classic model into the Medieval period. In addition, the paper examines the process of radical changes in the perception of space beginning in the Renaissance and under the impact of the long process of secularization and general demythologization referred to by the author as the Modernity era. The paper states that this process continued for some centuries emptying the space of myth and reached its highest peak by the end of the 19th century. The author provides a special insight on the reasons of the increased need for myth and cites as an example the emergence of geopolitics as a new discipline. Further, the author describes the main vector of space discourse development from the 20th century until now shaped by the Postmodernity. The article focuses on two particular spatial concepts such as "heterotopia" and "rhizome". According to the author they illustrate the main features of modern space - anti-hierarchy and openness to a new mythologization. The emphasis is put on the main differences of space perception between the postmodern and traditional society. The author makes an assumption that the space discourse of today will also influence the researches of actual global political and territorial architecture.